Representasi Hopelessness dalam MV BTS Spring Day (Analisis Semiotika Roland Barthes) - Sevilla, Vinta; Wahyuningratna, Ratu Nadya (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
Music Video is one of the effective communication tools to convey a message. In terms of cinematography,lyrics to properties can be a means to convey an idea. The messages conveyed varied, ranging from storiesof love, sadness, friendship to feelings of loneliness. One thing is extreme, messages such as disturbed mentalhealth to suicidal ideation can now be conveyed in a music video. One of them is the Spring Day music videobelonging to the South Korean boy band, BTS. This group, who always succeeds in putting their ideas intothe lyrics of their songs, wants to convey a message about how young people can lose hope because of a deeplonging for someone who means a lot to them. The researcher will analyze the music video using RolandBarthes' semiotic analysis to find a representation of hopelessness which is described in the lyrics andvisualization.